2020
DOI: 10.5194/gmd-13-363-2020
|View full text |Cite
|
Sign up to set email alerts
|

Are contributions of emissions to ozone a matter of scale? – a study using MECO(n) (MESSy v2.50)

Abstract: Abstract. Anthropogenic and natural emissions influence the tropospheric ozone budget, thereby affecting air quality and climate. To study the influence of different emission sources on the ozone budget, often source apportionment studies with a tagged tracer approach are performed. Studies investigating air quality issues usually rely on regional models with a fine spatial resolution, while studies focusing on climate-related questions often use coarsely resolved global models. It is well known that simulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The namelist setup used for the simulations is part of the Supplement. The model data used in this study are available under the following DOI: https://doi.org/10.5281/zenodo.3908469 (Mertens, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The namelist setup used for the simulations is part of the Supplement. The model data used in this study are available under the following DOI: https://doi.org/10.5281/zenodo.3908469 (Mertens, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More details about the emission inventory are provided by Hendricks et al (2017). Further details about the preprocessing of the emissions is given in Appendix A of Mertens (2017).…”
Section: Emission Scenarios and Numerical Experimentsmentioning
confidence: 99%
“…industrial and urban clusters) and quantify their impacts on non-linear photochemical processes, e.g. ozone production (Vinken et al, 2014;Visser et al, 2019;Mertens et al, 2020a) as well as on heterogeneous processes, e.g. par-V. Kumar et al: Regional model evaluation using MAX-DOAS ticulate nitrate production (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…isolated point sources, road networks and ship tracks) and facilitate understanding of sector-specific impacts on secondary pollution (e.g. ozone production) (Colette et al, 2014;Mertens et al, 2020a). However, comparison with in situ measurements showed that these gains could only be quantitatively determined up to a resolution of ∼ 7 × 7 km 2 , beyond which major improvements were not observed (Colette et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aircraft measurements were combined with satellite data of tropospheric NO 2 column densities from the Global Ozone Monitoring Experiment 2 (GOME-2; Munro et al 2016) and Sentinel-5P/Tropospheric Monitoring Instrument (TROPOMI; Veefkind et al 2012), and with cloud data retrieved from the SEVIRI Imager on the Meteosat Second Generation (MSG) satellite, as well as the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) on the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) (Winker et al 2010). The measurements were also used to evaluate the global chemistry climate model EMAC (Jöckel et al 2010) and the global-regional chemistry-climate model MECO(n) (Kerkweg and Jöckel 2012a,b;Mertens et al 2016).…”
mentioning
confidence: 99%